Caracterização fitossociológica e vegetacional de um fragmento florestal urbano de mata atlântica de interior - Paraná, Brasil - Boldarini, Fabiana Ruiz (2023)
The Parque Natural Municipal Paulo Gorski, located in western Paraná, comprises an urban remnant of Mixed Ombrophilous Forest. This study aimed to identify tree species and conduct the phytosociological characterization of this fragment of the Atlantic Forest. Monthly visits were made in ten plots (20 x 5 m) to collect fertile samples. A rarefaction curve was generated, and phytosociological parameters, diversity, and the distribution of individuals in diameter classes were calculated. A total of 158 tree individuals were sampled, distributed across 23 families and 47 species (including six exotic ones). Among the species found, 74.4% exhibited zoochoric dispersion syndrome, 19.1% anemochoric, and 6.5% autocoric. Concerning successional category, 63.8% were early successional species. Alchornea triplinervia (Spreng.) Müll.Arg. and Prunus myrtifolia (L.) Urb. had the highest importance values due to their high number of individuals, greater frequency, and basal area. Araucaria angustifolia (Bertol.) Kuntz, an endangered species, also had a high importance value. The Shannon diversity index was 3.43, and evenness was 0.89. Approximately 70% of the individuals were distributed in smaller diameter classes (< 15 cm), forming an inverted J-shape, an expected pattern indicating a regenerative capacity and structure of preserved forest remnants, despite being in an urban area and facing significant human pressures. This urban forest fragment should be preserved, as it contains native and endangered tree species from the region, serving as an ecological corridor, and maintains important ecological and social functions for the region